Disentangling the role of prokaryotes in regulating export flux via suspended and sinking organic matter in the southern ocean - Dithugoe, Choaro David (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The role of phytoplankton in regulating atmospheric carbon dioxide in the marine environment has been the subject of extensive research. We lack, however, comparative insights regarding the functional contributions of bacteria, archaea, fungi, and viruses (the microbiota) to organic matter export especially in understudied polar marine environments such as the Southern Ocean. This knowledge deficit is in part due to the high levels of microbial diversity which obscures efforts to study the relationship between diversity and ecosystem functions including their roles in the sequestration of carbon and nitrogen. Elucidating their precise contributions to organic matter export may be central to potential ecosystems feedbacks to global climate change. We examined several factors which may influence organic matter export to depth including net primary production, phytoplankton biomass, temperature, and prokaryotic functional capacity in the Southern Ocean. A Marine Snow Catcher was used to collect suspended and sinking material 10 metres below mixed layer depth at Southern Ocean Time Series (SOTS) in autumn (March-April) and in the Atlantic sector of the Southern Ocean in winter (July-August) and spring (October-November) 2019. The suspended and sinking material was used to determine the particulate organic carbon and nitrogen concentrations which were then used to calculate fluxes and export ratio ((e-ratio) - particulate organic carbon flux divided by net primary production). Additionally, genomic DNA was extracted from the suspended and sinking material and sequenced to obtain Shotgun metagenomic data which was employed to reconstruct metagenome assembled genome (MAGs) and their functional capacity using bioinformatic tools such as DRAM. Data from the Atlantic sector of the Southern Ocean, demonstrate that net primary production and temperature were inversely related to the e-ratio which is consistent with previous findings from the northern region of the Southern Ocean. Genomic functional capacity from SOTS suggested that r-strategist (organisms adapted to live in unstable environments) bacteria (e.g., Gammaproteobacteria) were prominent in the suspended pool. By contrast, the sinking particle-pool appeared to be dominated by K- strategists (organisms adapted to stable environment). The opposite was true for the archaea. This finding (i.e., bacteria) differs from a previous study in the northern region of the Southern Ocean, showing that microbes with K-strategists were more abundant in the suspended fraction. K-strategists typically degrade sinking organic matter into suspended organic matter or dissolved organic matter reducing the organic carbon export efficiency. Furthermore, Data from the Atlantic sector of the Southern Ocean revealed that seasonal temperature changes might dictate the rate of regional prokaryotic degradation across the zones. Resulting in rapid degradation at the northerly warmer regions and slow degradation further south. The data further provide evidence of chemolithoautotrophic mechanisms, with prokaryotes harbouring key pathways, required to transform dissolved inorganic carbon into complex organic forms, including recalcitrant dissolved organic carbon. Collectively, the SOTS and Atlantic sector of the Southern Ocean data suggest that shifts in prokaryotic community structure and functional capacity may regulate (either degradation or synthesis of organic matter) carbon export to depth.
Keywords: Microbial ecology; Bioinformatics; Biochemistry; Oceanography; Metagenomics; Carbon cycle (Biogeochemistry); Prokaryotes